STRATEGI DIRECTED READING THINKING AKCTIVITY (DRTA) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN KELAS V DI SEKOLAH LUAR BIASA TUNARUNGU - ARI PRASETYO, TEGAR (Jurnal Pendidikan Khusus, 2017)
Abstract : Impacts of deafness result in limited information obtained by children with hearing impairment. So that children understand the difficulty of reading the Indonesian subjects. This study aimed to analyze the influence of learning strategies in reading comprehension DRTA child Deaf class V SDLB-B Karya Mulia 1 Surabaya, especially in terms of reading comprehension in learning Indonesian. This study uses a quantitative approach to research the type of pre-experiment and design of the study one group pre-test - post-test design. Subject researched children with hearing impaired class V in SDLB-B Karya Mulia 1 Surabaya amounting to 8 eople. Test data collection techniques such as statistical data analysis techniques with the non-parametric Wilcoxon test formula The results of analysis of test match pairs data analysis showed that test early / pre-test Average -rata that obtained is 48 and after Given treatment test end / post test with the average obtained for 71 It Show that There Significant increase. Zh value = 2.521 more large compared to the value of Critical 5% Zt = 1.96 which means Ho is rejected and Ha accepted So could Said Existence influence use DRTA strategy against reading comprehension child Deaf class V in SDLB-B 1 Surabay a Noble Work   Keywords:, DRTA Strategies, Reading Comprehension